Reaping benefits from corporate blogs - Yin, Samuelson Chung Yao (2008)
With the growing popularity of individual blogs, companies have begun to utilize this nascent media to communicate with their stakeholders. This study aims at discovering how companies can best operate their corporate blogs in order to reap the greatest benefits from this media. From the literature review, corporate blogs are considered valuable platforms, and involvement with them is thought to be the main benefit to a firm's operation. Three characteristics of blogs have been shown to influence involvement, and these results can serve as a guideline for corporate blogging. Self-related information, a centralized style of management, and frequent updating are recommended as vital factors in creating a successful corporate blog.